Implementing Low-Cost Rural Land Certification : The Case of Ethiopia - Deininger, Klaus (World Bank, Washington, DC, 2012)
This report is about implementing low-cost rural land certification. Prior to 1975, Ethiopia's land tenure system was complex and semi-feudal. Tenure was highly insecure, arbitrary evictions were common, and many lands underutilized. High inequality of land ownership reduced productivity and investment, leading to political grievances and eventually the overthrow of the imperial regime in 1975. The Marxist government that took power transferred ownership of all rural land to the state, leading to declines in productivity and soil degradation. A 1997 federal proclamation (law) devolved responsibility for land policy to the regions. Although this has led to considerable inter-regional diversity, a number of common issues emerge, namely (i) administrative land redistribution is not an empty threat; (ii) while land rental is now allowed, the fact that in most regions the amount that can be rented is limited and that land rights are contingent on physical residence in the village could undercut efforts at non-agricultural development and migration from rural areas; and (iii) mortgaging and sale of land are universally prohibited